2023
DOI: 10.3390/ani13050812
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Underwater Vocalizations in Chinese Soft-Shelled Turtle (Pelodiscus sinensis)

Abstract: Sound communication is important for underwater species. The wild population of the Chinese soft-shelled turtle (Pelodiscus sinensis) is listed as vulnerable. However, its vocalization, which can serve as the basis for ecological and evolutionary research, has not been studied. Here, we performed underwater recordings of 23 Chinese soft-shelled turtles of different ages and sexes and identified 720 underwater calls. The turtle calls were manually divided into 10 call types according to visual and aural inspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…It is also worth noting that these free-moving turtles were only one-month-old suggesting that vocal complexity may increase during development and highlighting the necessity of studying the use of sounds in turtles across different life stages. Moreover, studies in freshwater turtles that were living in captivity as a group found that the use of sound types varies by sexes and ages [4850]. These findings support our expectation that turtles have wider use of sounds in their underwater lives and suggest the potential of social communication by acoustic signals in turtles.…”
Section: Future Directions and Conclusionsupporting
confidence: 81%
“…It is also worth noting that these free-moving turtles were only one-month-old suggesting that vocal complexity may increase during development and highlighting the necessity of studying the use of sounds in turtles across different life stages. Moreover, studies in freshwater turtles that were living in captivity as a group found that the use of sound types varies by sexes and ages [4850]. These findings support our expectation that turtles have wider use of sounds in their underwater lives and suggest the potential of social communication by acoustic signals in turtles.…”
Section: Future Directions and Conclusionsupporting
confidence: 81%
“…In aquaculture, the Chinese soft-shell turtle (Pelodiscus sinensis) is the top aquatic economic species of amphibians and reptiles in China, with an annual output exceeding 300,000 tons for ten consecutive years [1,2]. However, there is marked sexual dimorphism in body growth and calipash when comparing male and female P. sinensis, and males have higher economic and industrial value than females [3][4][5]. Therefore, there is an urgent need to breed monosexual populations of male P. sinensis to benefit the entire aquaculture industry [6,7].…”
Section: Introductionmentioning
confidence: 99%